Associations between different types of hypoglycemic agents and the clinical outcome of percutaneous coronary intervention in diabetic patients—From the FU-Registry. Issue 5 (May 2015) - Ike, Amane; Shirai, Kazuyuki; Nishikawa, Hiroaki; Iwata, Atushi; Yahiro, Eiji; Sugihara, Makoto; Kawamura, Akira; Uehara, Yoshinari; Zhang, Bo; Ogawa, Masahiro; Mori, Ken; Miura, Shin-ichiro; et al.
Abstract: Background: It is not clear whether it is reasonable to use particular drugs for glycemic control in preference to other hypoglycemic agents in terms of the clinical outcome of percutaneous coronary intervention (PCI) in patients with diabetes mellitus (DM). Methods and results: Among 2148 patients (2568 lesions) in the FU-Registry, DM patients who underwent PCI ( n  = 758; 922 lesions) were investigated to clarify the effects of various drugs for glycemic control on the clinical outcome [major adverse cardiac events (MACEs): death, myocardial infarction (MI), and target lesion revascularization (TLR)] over approximately 300 days of follow-up (UMIN000005679). The MACEs(+) group ( n  = 165) had a higher usage of insulin ( p  < 0.001) and a lower usage of biguanides (BG, p  < 0.05) and dipeptidyl peptidase-IV inhibitors ( p  < 0.05) at PCI, compared to the MACEs(−) group ( n  = 593). A multivariate logistic regression analysis showed that low-density lipoprotein cholesterol, insulin use, atherosclerosis obliterans, and lesion reference might be significantly associated with MACEs, while BG use was negatively correlated with MACEs ( p  = 0.04). The cumulative frequency of MACEs in the insulin-treated group was significantly higher ( p  < 0.05) than that in the non-insulin group, and the strongest association between insulin with MACEs was seen in the hemoglobin (Hb) A1c 6.5–7.5% group. There tended to be a negative correlation between the use of insulin and MACEs, with risk ratios of <1, for the HbA1c >8.5% groups. Conclusions: Among different hypoglycemic agents, treatment with insulin was associated with poor mid-term clinical outcomes in DM patients who underwent PCI, while BG use was negatively correlated with MACEs. It may be reasonable for patients with HbA1c >8.5% to avoid hyperglycemia and glucotoxicity, even through the use of insulin.